Physical modelling of slag-foaming phenomenon resulted from inside-origin gas formation reaction. (21st April 2017) - Qiu, G.; Shan, C.; Zhang, X.; Lv, X.
Abstract : Slag foaming is a common phenomenon in the metallurgical process that negatively influence the blast furnace when smelting some special ores such as V-Ti-magnetite. Inside-origin gas plays a leading role during this foaming phenomenon. This study performed a room-temperature simulation of slag foaming from inside-origin gas. Results showed that foaming height increased with increased the amount of inside-origin gas. Higher liquid viscosity caused lower foaming height, which was opposite to the slag-foaming regularity caused by outside-origin gas. Higher surface tension benefited the suppression of the foaming phenomenon and shortened the foaming elimination time. The effect of solid particles on the foaming phenomenon was not monotonic, i.e. the maximum foaming height initially increased and then decreased with increased number of particles. Particles with better solution wettability caused higher foam because they can easily adhere onto film, thereby enhancing elasticity and extending film life. Small particle size benefited the foam. The experimental data were in accordance with the model predictions based on the estimated bubble sizes, which proved that the model developed by Zhu and Du helped predict foaming height caused by chemical reaction.